Soil erosion sensitivity of rubber plant, oil palm, and teak in Ogan Komering Ilir District - Satria Jaya Priatna; Ahmad Sepriansyah (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2024)
Soil erodibility was the ease with which soil erodes. The study aimed to determine the value of soil erodibility on rubber, oil palm, and teak land at PT Waimusi agroindah. The method used was a very detailed survey, assisted by digital maps. Soil samples were taken based on the study area. Soil samples were taken at 0–30 cm deep and topsoil for soil permeability analysis as well as the completeness of the tools and materials needed. The calculation of the value of soil erodibility on rubber, oil palm, and teak land has moderate criteria. The equation of these criteria in quantitative numbers for oil palm land has a value of 0.18, which was higher than rubber land at 0.15 and teak land at 0.13. While on forest land, the soil erodibility value was 0.04, so it falls into very low criteria. The conclusion of this research was that rubber, oil palm, and teak land obtained soil erosion sensitivity values with moderate criteria, and the results of soil erosion sensitivity values on forest land were classified as very low. This research was one of a series of several factors used to determine the potential for land erosion. Further research needs to be done so that the potential for erosion could be determined from all the factors that affect the potential for erosion.